A review of patient-reported outcomes used for regulatory approval of oncology medicinal products in the European Union between 2017 and 2020 - Teixeira, Maria Manuel; Borges, Fábio Cardoso; Ferreira, Paula Sousa; Rocha, João; Sepodes, Bruno; Torre, Carla (Frontiers in Medicine, 2022)
Introduction: Cancer and corresponding available treatments are associated with substantial symptoms and functional limitations. In this context, collection of patient-reported outcomes (PRO) in clinical trials gained special interest and is recommended by regulatory authorities. Within clinical trials framework, PRO may provide evidence to support medicines approval, labelling and marketing claims. This study aims to analyse the existing evidence based on PRO as part of new oncology indications receiving positive opinions issued by the European Medicines Agency (EMA) between 2017 and 2020 and to identify PRO related label claims granted. Methodology: Oncology medicinal products and indications approved by the European Commission following a positive opinion from the EMA between 2017 and 2020 were identified. European Public Assessment Report (EPAR) and Summary of Product Characteristics (SmPC) were reviewed for each medicinal product to identify use of PRO and PRO label claims. Results: A total of 128 oncology indications, corresponding to 76 medicines, were approved; of those, 100 (78.1%) included PRO in the confirmatory clinical trials. Thirty-seven indications were supported by double-blind randomised trials and the remainder 63 by open-label trials. Out of the 104 confirmatory trials analysed, PRO were defined as a secondary endpoint in 60 studies (57.7%), exploratory in 31 (29.8%) and as both in 13 (12.5%). In total, 54 different PRO measures (PROM) were used, of those 41 (75.9%) were disease-specific measures. Nevertheless, PROM selected relied on the EORTC (41.3%), FACIT (17.1%) and EQ-5D (29.2%) measures. A total of 76 indications (59.4%) had PRO reviewers comments included in the EPAR, however only 22 indications (17.8%) included label claims in the SmPC. The reasons identified in the EMA assessment supporting the exclusion of PRO claims were described for 34 indications (44.7%). Conclusions: Despite growing recognition of the value of PRO data for the development of improved cancer therapies, PRO implementation remains challenging. The main reasons identified in our study are related with study design, missing data, study conduct and PROM selection.